Examining Public Service Innovations in Indonesia: Challenges, Characteristics, and Implementation within Bureaucratic Systems - Asmara, Anugerah Yuka; Handoyo, Setiowiji; Purwadi, Purwadi; Dinaseviani, Anggini; Jayanthi, Ria; Kusumawardhani, Dhian (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
In the twenty-first century, public sector organizations (PSOs) have embraced various innovations to enhance productivity, efficiency, and accountability. Indonesia’s local and central governmental agencies have incorporated public service innovations into their systems, achieving notable improvements. The Ministry of State Apparatus Empowerment and Bureaucratic Reform (Kementerian PANRB) reported 3478 public service innovations through the Public Service Innovation Competition Program (KIPP) by 2022. These innovations have led to significant enhancements in service delivery, increasing productivity by streamlining processes, boosting efficiency by reducing bureaucratic delays, and improving accountability through better transparency and governance. This research employs a post-positivist paradigm with a descriptive methodology, collecting data through interviews and secondary sources. The findings indicate that PSOs can successfully implement innovations within the constraints of Indonesian bureaucracy. These innovations have improved service quality and responsiveness and introduced concepts like public service modification, offering detailed insights into achieving substantial public service changes amidst complex bureaucratic challenges.